MATH SOLVE

4 months ago

Q:
# The solution to a system of equations is (6-3). Choose two equations that might make up the system. Y= -3x+6 Y=2x-9 y=-5x+27 y=2x-15 y=-4x+27

Accepted Solution

A:

Answer: C) y = -5x + 27 and D) y = 2x - 15Step-by-step explanation:Substitute x = 6 and y = -3 into each of the given equations to see which result in a TRUE statement.A) y = -3x + 6 -3 = -3(6) + 6 -3 = -18 + 6 -3 = -12 FALSEB) y = 2x - 9 -3 = 2(6) - 9 -3 = 12 - 9 -3 = 3 FALSEC) y = -5x + 27 -3 = -5(6) + 27 -3 = -30 + 27 -3 = -3 TRUE!D) y = 2x - 15 -3 = 2(6) - 15 -3 = 12 - 15 -3 = -3 TRUE!E) y = -4x + 27 -3 = -4(6) + 27 -3 = -24 + 27 -3 = 3 FALSE